Some solutions for further attracting Foreign Direct Investments in Binh Dinh province in the coming time - Nguyen, Thanh Vinh (Trung tâm Đào tạo và Giáo dục quốc tế, 2017)
Besides technical infrastructure, investment environment is significant influenced by social infrastructure. Social infrastructure includes health systems and health care service for people, education and training system, recreation and other services. Moreover, socio-moral values, custom. religion, culture., also help make up the common picture of the social infrastructure of a country or locality^